Analisis Pengaruh Kebijakan Pajak Terhadap Investasi Teknologi Digital Di Era Industri - Naella Amalia Sri Amai; Eva Aditya Putri; Dien Noviany Rahmatika (Universitas Kristen Indonesia Toraja, 2024)
The industrial era 4.0 has triggered major transformation in various sectors, especially through the adoption of digital technologies such as the Internet of Things (IoT), artificial intelligence (AI), big data, and cloud computing. Investments in digital technology have become very important for companies to increase operational efficiency and global competitiveness. Favorable tax policies can play a significant role in encouraging companies to invest in these technologies. Tax incentives such as tax deductions for research and development (R&D) and tax credits for technology investments can help reduce the financial burden on companies and encourage them to allocate more resources into digital technology. However, the implementation of supportive tax policies often faces challenges such as a lack of awareness and understanding of taxpayers, the complexity of tax administration, and policy instability. Socialization and education regarding the benefits of tax incentives, simplification of administrative procedures, and policy stability are very important to increase the effectiveness of tax policies. Supportive regulations, such as intellectual property rights protection and cybersecurity, also play an important role in creating confidence among investors and companies. Collaboration between the government and the private sector can produce policies that are more suited to needs on the ground and increase the use of tax incentives. Although the Indonesian government has recognized the importance of digital technology and introduced various initiatives, there are still significant challenges to overcome. This research analyzes the influence of tax policy on digital technology investment in the industrial era 4.0, with the aim of providing recommendations for more effective and efficient policies in supporting digital transformation in Indonesia.